Geology A Fundamental Guide for Engineering Students - Mohd Firdaus Md Dan@Azlan,; Aziman Madun, (2023)
"Engineering Geology: A Fundamental Guide for Engineering Students" is a valuable resource that introduces engineering students to the fascinating realm of geology. The book covers a wide range of themes, beginning with an examination of the universe, the solar system, and the introduction of the Earth. The exciting idea of plate tectonics and its impact on geological risks is explored by readers. Throughout, the role of engineering geology in civil engineering activities is highlighted. Chapter 2 focuses on minerals, their nature, origin, identification, and classification, laying the groundwork for understanding rock-forming minerals found on Earth. Chapter 3, readers study the three major types of rocks: igneous, sedimentary, and metamorphic, with a focus on their applications in civil engineering. Chapter 4 focuses on weathering processes, their impact on rock mass and its classification, which is critical for engineering considerations. Chapter 5 explores geological structures such as folds, faults, joints, and unconformities before concluding with geological mapping techniques. Throughout the book, thought-provoking review questions reinforce crucial themes. This comprehensive guide prepares aspiring engineers to address geotechnical difficulties, resulting in a safer, more resilient, and sustainable society.